1997
DOI: 10.1097/00000542-199712000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Analgesic Activity of Morphine-6-glucuronide after Short-term Intravenous Administration in Healthy Volunteers 

Abstract: Background The analgesic activity of morphine-6-glucuronide (M-6-G) is well recognized for its contribution to the effects of morphine and its possible use as an opioid analgesic with a wider therapeutic range than morphine. The present study attempted to quantify the relative contribution of M-6-G to analgesia observed after systemic administration of morphine. Methods In a placebo-controlled, sixfold crossover study in 20 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 54 publications
2
37
0
Order By: Relevance
“…Morphine-3-glucuronide has no clinical effect and does not influence morphine effects. 31,32 Morphine-6-glucuronide is an active metabolite, but crosses the blood–brain barrier slowly and is considered noncontributory to the short-term effects of morphine, 33-35 and, the observed morphine-6-glucuronide concentrations were never more than 10% of the median EC 50 for miosis reported previously. 30 Therefore, morphine-6-glucuronide was not included in the model, as described previously.…”
Section: Methodsmentioning
confidence: 84%
“…Morphine-3-glucuronide has no clinical effect and does not influence morphine effects. 31,32 Morphine-6-glucuronide is an active metabolite, but crosses the blood–brain barrier slowly and is considered noncontributory to the short-term effects of morphine, 33-35 and, the observed morphine-6-glucuronide concentrations were never more than 10% of the median EC 50 for miosis reported previously. 30 Therefore, morphine-6-glucuronide was not included in the model, as described previously.…”
Section: Methodsmentioning
confidence: 84%
“…These studies have demonstrated both an analgesic efficacy, 18,[33][34][35][36] a lack of analgesic effect of M6G, 37,38 or a peripherally-mediated analgesic effect 39 over a wide range of M6G bolus or infusion regimes. The analgesic activity of single doses of M6G has also been demonstrated when administered i.v.…”
Section: C L I N I C a L P A I N S T U D I E Smentioning
confidence: 99%
“…Thus, when M6G was injected in humans by Lötsch et al to yield plasma concentrations equivalent to those following an analgesic morphine dosage, no analgesic activity was observed. [51] Motamed et al also found injection of M6G was ineffective for postoperative pain relief in humans. [52]…”
Section: Heroin and Its Metabolismmentioning
confidence: 99%